2006
DOI: 10.1210/jc.2005-2287
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Oral Conivaptan: A V1A/V2Vasopressin Receptor Antagonist, Assessed in a Randomized, Placebo-Controlled Trial in Patients with Euvolemic or Hypervolemic Hyponatremia

Abstract: Oral conivaptan (40 and 80 mg/d) was well tolerated and efficacious in correcting serum [Na(+)] in hyponatremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
150
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(161 citation statements)
references
References 19 publications
4
150
0
7
Order By: Relevance
“…All agents of this class are inhibitors of the cytochrome P450 3A4 (CYP3A4) system, but conivaptan appears to be the most potent in this regard. Although the drug is orally active, 109 to minimize the possibility of drug interactions, the FDA has restricted its distribution to a parenteral form for shortterm (4-day) in-hospital use only. The remaining V 2 R antagonists appear to have more limited CYP3A4 interactions and are currently being developed for long-term oral use.…”
Section: Development Of Vasopressin Receptor Antagonistsmentioning
confidence: 99%
“…All agents of this class are inhibitors of the cytochrome P450 3A4 (CYP3A4) system, but conivaptan appears to be the most potent in this regard. Although the drug is orally active, 109 to minimize the possibility of drug interactions, the FDA has restricted its distribution to a parenteral form for shortterm (4-day) in-hospital use only. The remaining V 2 R antagonists appear to have more limited CYP3A4 interactions and are currently being developed for long-term oral use.…”
Section: Development Of Vasopressin Receptor Antagonistsmentioning
confidence: 99%
“…In several double-blind, placebo-controlled clinical trials, conivaptan has been effective in improving serum sodium concentrations [91]. Serum sodium is improved by 6.3 mmol/L with a 40 mg daily dose, and by 9.0 mmol/L with an 80 mg daily dose [92][93][94]. Importantly, despite the properties of conivaptan as a V1a-receptor antagonist, it had no effect on systolic blood pressure or pulse rate.…”
Section: Vasopressin Receptor Antagonistmentioning
confidence: 99%
“…1), 18 trials met the eligibility criteria or reported data for an eligible subgroup. Two trials assessed conivaptan, 13,14 four assessed lixivaptan, [15][16][17][18] three assessed satavaptan [19][20][21] and nine assessed tolvaptan. [22][23][24][25][26][27][28][29] There were no RCTs published assessing other known interventions such as urea, sodium tablets or mannitol.…”
Section: Resultsmentioning
confidence: 99%
“…Otsuka (manufacturer of tolvaptan and funder of this review) provided information for six trials of tolvaptan vs placebo and the authors of two further trials responded. 14,20 A summary of the characteristics of the included trials is presented in Table 1. All 18 trials were randomized multicentre trials.…”
Section: Resultsmentioning
confidence: 99%